EFFECT OF FERTILIZATION AND SUPPLEMENTARY FEEDING ON GROWTH PERFORMAMNCE OF LABEO ROHITA, CATLA CATLA AND CYPRINUS CARPIO - S. Abbas; M. Ashraf; I. Ahmed (Journal of Animal and Plant Sciences, 2014)
Studies were conducted to investigate the efficacy of inorganic and organic fertilizers on fish growth when applied individually and/or when combined with supplementary feed. Studies were designed and executed in earthen ponds and continued for one full growth period. Results revealed that organic manure is better than inorganic fertilizers and can independently handle nutritional requirements of fish to some extent of their growth period but inorganic fertilizers can not do this alone. These studies further exposed that administration of supplementary feed is mandatory for maximum yield though both fertilizers have been provided. Supplementary/artificial feed not only fulfills the nutrient deficiencies but also helps to exploit the maximum potential of manures added into the pond.
Keywords: Organic manures; inorganic fertilizers; supplementary feed; Indian and Chinese carps